Overview of Animal Models of Obesity - Lutz, Thomas A. (2012)
This is a review of animal models of obesity currently used in research. We have focused upon more commonly utilized models since there are far too many newly created models to consider, especially those caused by selective molecular genetic approaches modifying one or more genes in specific populations of cells. Further, we will not discuss the generation and use of inducible transgenic animals (induced knock-out or knock-in) even though they often bear significant advantages compared to traditional transgenic animals; influences of the genetic modification during the development of the animals can be minimized. The number of these animal models is simply too large to be covered in this chapter.